2018
DOI: 10.1002/ijc.31617
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte telomere length associates with nasopharyngeal carcinoma risk and survival in Hong Kong Chinese

Abstract: Telomere shortening occurs as an early event in tumorigenesis. The TERT-CLPTM1L locus associates with nasopharyngeal carcinoma (NPC) risk. It remains unknown if leukocyte telomere length (LTL) associates with NPC risk and survival. The relative LTL (rLTL) was measured by quantitative-PCR in 2,996 individuals comprised of 1,284 NPC cases and 1712 matched controls. The odds ratio (OR) and 95% confidence intervals (CI) were calculated by logistic regression. The hazard ratio (HR) and 95% CI were calculated by Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Telomere length in NPC patients is 3.2 times shorter than in normal tissue; this indicates that telomere shortening is involved in tumor progression. Ko et al studies suggest that telomere shortening is associated with old age and males [21].…”
Section: Discussionmentioning
confidence: 99%
“…Telomere length in NPC patients is 3.2 times shorter than in normal tissue; this indicates that telomere shortening is involved in tumor progression. Ko et al studies suggest that telomere shortening is associated with old age and males [21].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have evaluated the association of LTL with the prognosis of other cancers and most showed that shorter LTL was associated with increased risks of death in cancer patients, including bladder cancer [46], stage I and II cutaneous melanoma [47], gastric cancer [48], colorectal cancer [49], renal cell carcinoma [50], pancreatic cancer [51], and lung adenocarcinoma [52]. Interestingly, a recent large study of nasopharyngeal carcinoma in Hong Kong found that suboptimal LTL (both too short and too long) was associated with poor survival compared to patients with normal range LTL [53]. Only a couple of studies reported that shorter LTL increased risk of relapse [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…According to Gihbid et al, EBV DNA plasma levels in patients above 30 years old are 4 times higher than in patients under 30 years. [17][18][19][20][21][22][23] The genetic factors of the patient are important in the development of NPC. The ends of DNA chains that contain proteins that protect DNA from damage are known as telomeres.…”
Section: 19mentioning
confidence: 99%
“…Telomere shortening is caused by the aging process and is associated with male gender. 22 Lymphocytes play an important role in the immune system because they influence the immune response to infectious microorganisms and other foreign substances. The specific lymphocyte response functions to attack microorganisms, protect against tumors, and cause tissue rejection after organ transplantation.…”
Section: 19mentioning
confidence: 99%